A flexible and salt-rejecting electrospun film-based solar evaporator for economic, stable and efficient solar desalination and wastewater treatment. (March 2021) - Li, Dengyu; Zhang, Xuejiao; Zhang, Siyu; Wang, Dongsheng; Wang, Zhenyu; Liu, Ying; Yu, Xuefeng; Zhao, Qing; Xing, Baoshan
Abstract: Recently, interfacial solar evaporation has been developed for water treatment. However, the high cost and low stability of solar evaporators significantly hinder their practical applications. In this study, layered graphene and polymethylmethacrylate were used to fabricate a composited film (GF) by electrospinning, which acted as a solar absorber. Together with a water transporter (polyurethane sponge) and a thermal insulator (polystyrene foam), the GF-based evaporator was constructed for solar distillation. Taking advantage of the porous three-dimensional structure of GF, the light path could be extended, rendering an efficient broadband solar absorption (92%). More importantly, although the content of layered graphene in the GF-based evaporator (1.75 g m −2 ) was only 5.8–17.5% of that in the current reported graphene-based evaporators (10–30 g m −2 ), a comparable water evaporation efficiency was acquired, which was induced by the much higher utilization efficiency of photothermal nanomaterials in the GF-based evaporator than that in the reported devices, ensuring its economic feasibility. Meanwhile, more than 99.9% heavy metal ions and 99.8% organic dye could be removed by the GF-based evaporator. Combining the merits of long-term and stable evaporation, salt rejection, and resistance to harsh environment, the GF-based evaporator was promising for freshwater recycling from both seawater and wastewater. Graphical abstract: Fabrication process of the GF-based evaporator and the description of solar distillation. Image 12 Highlights: The 3D network structure of the fibers was in favor of maximizing the light absorbance and reducing the cost of materials. The solar absorber showed extraordinary stability against high salinity, acid and base solutions. The cost-effectiveness of the whole device in our study was much higher than that in most previous reports.